Evaluation of Biochemical Traits of Three Sweet Pepper (Capsicum annuum L.) Varieties in Bangladesh (Journal of the Bangladesh Agricultural University, 2025)
Three hybrid varieties (F1; green, yellow and red colour) of sweet pepper (Capsicum annum), which processes great economical and nutritional potentialities, were taken in this study to assess their nutritional quality based on some biochemical parameters. Fresh capsicum of all three varieties were directly purchased from the greenhouse-shed of Shaurav Fishers and Agro Ltd, Trishal, Mymensingh. Vitamin C was determined by redox titrate method, total sugar (620 nm, anthrone solution), reducing sugar (510nm, dinitro salicylic acid solution), β-carotene (510nm, 480nm, acetone solution) and lycopene (663nm, 645nm, 505nm, 453nm, acetone and hexane solution) were estimated using a UV-visible spectrophotometer in the post-graduate laboratory of Bangladesh Agricultural university, Mymensingh. All the varieties showed variations significantly (p≤0.05) among the studied parameters set with complete randomized design. The range of mean performance for the following biochemical parameters was determined to be: vitamin C 136.151–252.89 mg, titratable acidity 0.1–0.6%, total sugar 0.99–2.23%, reducing sugar 1.51- 2.35%, βeta–carotene 1.03-8.40 μg g–1 and lycopene 0.001–0.15 mg 100 ml–1. According to Duncan Multiple Range Test the parameters showed efficiency at 1% level of significance. From the overall ranking based on efficiency score red capsicum was the best one followed by yellow and green. Therefore, it could be concluded that among the three-capsicum varieties, the red variety possess more nutritional value.J Bangladesh Agril Univ 23(1): 42–49, 2025